2018
DOI: 10.1002/dvdy.24615
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase Mov10 is essential for gastrulation and central nervous system development

Abstract: Mov10 is essential for gastrulation and normal CNS development. Developmental Dynamics 247:660-671, 2018. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Through Cross-Linking ImmunoPrecipitation (CLIP) experiments, it has been established that FMRP and MOV10 share a common RNA interactome. Unlike FMRP, the Mov10 knockout (KO) is embryonic lethal [ 15 , 16 ]; however the Mov10 heterozygous (Het) mouse has increased anxiety and hyperactivity, which are features shared with Fragile X syndrome [ 17 ] and suggest impaired neuronal function [ 15 ]. We were thus interested in investigating the consequences of Mov10 and Fmr1 reduction on dendritic development.…”
Section: Introductionmentioning
confidence: 99%
“…Through Cross-Linking ImmunoPrecipitation (CLIP) experiments, it has been established that FMRP and MOV10 share a common RNA interactome. Unlike FMRP, the Mov10 knockout (KO) is embryonic lethal [ 15 , 16 ]; however the Mov10 heterozygous (Het) mouse has increased anxiety and hyperactivity, which are features shared with Fragile X syndrome [ 17 ] and suggest impaired neuronal function [ 15 ]. We were thus interested in investigating the consequences of Mov10 and Fmr1 reduction on dendritic development.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the Mov10 heterozygous knockout mice showed increased genomic L1 content, decreased hippocampal dendritic arborization as well as behavioral deficits suggesting an important role for MOV10 in the formation of normal brain circuitry. The importance of MOV10 in the development of CNS was also demonstrated in X. laevis (Skariah et al, 2018). MOV10's absence in tadpoles led to shorter body length and smaller eyes.…”
Section: Mov10's Role In Organisms and During Developmentmentioning
confidence: 79%
“…A critical role for MOV10 in development was first discovered by the embryonic lethality of a full body Mov10 knockout mouse (Skariah et al, 2017). To identity the developmental step where MOV10 was required, the authors turned to Xenopus laevis (Skariah et al, 2018). They used morpholinos to block the maternal Mov10 mRNA in X. laevis embryos and found that they failed to complete gastrulation.…”
Section: Mov10's Role In Organisms and During Developmentmentioning
confidence: 99%
“…To date, a lot of the identified RNA helicases belong to the SF2, only a dozen of SF1 RNA helicases have been identified. Among them, MOV10 and MOV10L1 both encode SF1 RNA helicases, which involved in various kinds of biological contexts, such as defense of RNA virus invasion, early development, neuron system, germ cell [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of maternal mov10 in xenopus embryos led to gastrulation defects, likely resulting from the large scales changes in mRNA expression due to Mov10’s role in miRNA mediated regulation of maternal-zygotic transition. In addition, zygotic Mov10 is necessary for development of the central nervous system [ 9 ]. In mouse, the Mov10 knockout one led to embryonic lethality, suggesting MOV10 is critical for early development.…”
Section: Introductionmentioning
confidence: 99%